DEVELOPMENT AND SUPERVISION OF THE SCHOOL PRINCIPLE TO IMPROVE THE DISCIPLINE OF INTEGRATED ISLAMIC ELEMENTARY SCHOOL TEACHERS, LENEK DISTRICT, LOMBOK TIMUR REGENCY - Saeful Fahmi (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to describe principals' coaching and supervision to improve SDIT Aikmel teachers' discipline. The research method is qualitative data collection by conducting interviews, observation, and documentation. The data analysis used in this research is data condensation, data display, and conclusion. Checking the validity of the data is done by credibility, transferability, dependability, and confirmability test. The results of this study indicate that the coaching carried out by the principal shows very significant results. This is because the principal has succeeded in creating harmonious relationships in interpersonal relationships, analyzing the needs of teachers, developing strategies used, and assessing and revising activity programs. Furthermore, the principal's efforts are helping teachers to plan and develop learning programs. The principal's supervision is carried out with individual supervision techniques by conducting class visits, group discussions, and training.